Using Self-Correction and Peer-Correction Techniques to Improve Students’ Writing Skills: A Comparative Study - Ade Yanti; Abdul Hadi; Dodi Settiawan (Indonesian Journal of Integrated English Language Teaching, 2022)
This research aimed to examine and compare the effects of using self-correction and peer-correction techniques on improvement of  students’ writing skills at Language Development Centre of a state Islamic university in Sumatera. The data were gathered using pre-test, post-test, writing assessment sheet and guidance sheet of self and peer correction techniques. This quantitative research was carried out by using an experimental method. The population consisted of 34 classes, and the samples were taken through cluster random sampling. As a result, 3 classes, consisting of 77 second-semester students, were selected. The research hypotheses were tested by using the Wilcoxon and Mann-Whitney tests. The results showed that, first, there was a significant difference in the students’ writing skills before and after using the self-correction technique. Second, there was a significant difference in students’ writing skills before and after using the peer-correction technique. Third, there was a significant difference in writing skills between the students who were taught using the self-correction technique and those who were taught using the peer-correction technique. The results also showed that the peer-correction technique had a more significant effect size on the scores for the students’ writing skills. Keywords: self-correction technique, peer-correction technique, students’ writing skill